2022
DOI: 10.5194/acp-2022-147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of clouds and precipitation on the aerosol concentrations and composition in a boreal forest environment

Abstract: Abstract. Atmospheric aerosol particle concentrations are strongly affected by various wet processes, including wet scavenging (below and in-cloud) and aqueous phase oxidation in-cloud. This study employs airmass history analysis and observational data to investigate how wet scavenging and cloud processes affect particle concentrations and composition during transport to a rural boreal forest site in northern Europe. Long term particle size distribution (~ 15 years) and composition measurements (~ 8 years) wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Precipitation is an important atmospheric process that drives the intra-and inter-annual trends of air pollutants. Recent work by Isokääntä et al 50 showed that wet deposition, including wet scavenging (below and in-cloud) and aqueous phase oxidation in-cloud, may strongly influence aerosol particle concentrations, size distribution and chemical composition. Thus, PAH chemistry and transformation are closely related to atmospheric conditions, including precipitation intensity, amount and frequency.…”
Section: Correlation Analysis Between Pahs Meteorological Parameters ...mentioning
confidence: 99%
“…Precipitation is an important atmospheric process that drives the intra-and inter-annual trends of air pollutants. Recent work by Isokääntä et al 50 showed that wet deposition, including wet scavenging (below and in-cloud) and aqueous phase oxidation in-cloud, may strongly influence aerosol particle concentrations, size distribution and chemical composition. Thus, PAH chemistry and transformation are closely related to atmospheric conditions, including precipitation intensity, amount and frequency.…”
Section: Correlation Analysis Between Pahs Meteorological Parameters ...mentioning
confidence: 99%